Glycolytic potential and ultimate muscle pH values in red deer (Cervus elaphus) and fallow deer (Dama dama) - Wiklund, Eva; Manley, Timothy R.; Littlejohn, Roger P. (Rangifer, 2004)
The ultimate pH value of meat (measured at approx. 24 hours post slaughter) gives information about the technological quality, i.e. shelf life, colour, water-holding properties and tenderness and is a direct consequence of muscle glycogen (energy) levels at slaughter. It may therefore also indicate whether or not the animal has been exposed to stressful energy depleting events prior to slaughter. In the present study, 141 animals (130 red deer (Cervus elaphus) and 11 fallow deer (Dama dama) were included to investigate the relationship between ultimate pH and residual glycogen concentration in red deer and fallow deer M. longissimus. In addition, the muscle glycogen content and ultimate pH values in three red deer muscles (Mm. triceps brachii, longissimus and biceps femoris) were studied. M. triceps brachii had higher ultimate pH and lower glycogen content compared with the other two studied muscles. The frequency of intermediate DFD (5.8≤ pH<6.2) was 5.4% in red deer M. longissimus, compared with 9.1% in fallow deer, while the frequency of DFD (pH≥ 6.2) was much lower in red deer (3.8%) than in fallow deer (54.5%). A curvilinear relationship between ultimate pH and total glucose concentration (glycogen and glucose) 30 min post slaughter in red deer and fallow deer M. longissimus was found. The relationship between muscle pH and lactic acid concentration however, was indicated to be linear. A significant variation in total glucose concentration at ultimate pH below 5.80 was observed, including values in the range from 18 to 123 mmol/kg wet tissue. It was concluded that further studies are needed to further explore the relationship between muscle glycogen content and technological and sensory quality attributes of meat from different deer species.Abstract in Swedish / Sammanfattning:Köttets pH-värde (mätt ca 24 timmar efter slakt) har stor betydelse för den teknologiska kvaliteten som t. ex. hållbarhet, färg, vattenhållande förmåga och mörhet. Glykogenförrådet (energinivån) i djurens muskulatur vid slakt är helt avgörande för köttets slutliga pH-värde. Därför kan pH-värdet också indikera om hanteringen av slaktdjur varit skonsam eller om stora mängder muskelenergi har förbrukats vid stress. I vår undersökning ingick 141 hjortar (130 kronhjortar (Cervus elaphus) och 11 dovhjortar (Dama dama) för att studera sambandet mellan köttets pH-värde och glykogeninnehållet i M. longissimus. Glykogeninnehåll och pH-värden i 3 muskler från kronhjort (Mm. triceps brachii, longissimus och biceps femoris) undersöktes också. M. triceps brachii hade högre pH-värde och lägre glykogeninnehåll jämfört med de två andra musklerna. Det var inte så stor skillnad i frekvensen av intermediär DFD (pH-värden mellan 5,8 og 6,2) mellan de två hjortarterna (5,4% för kronhjort och 9,1% för dovhjort), däremot var frekvensen av DFD (pH-värden över 6,2) mycket låg hos kronhjort (3,8%) jämfört med dovhjort (54,5%). Det fanns ett kurvlinjärt samband mellan slutligt pH-värde i köttet och total glukoskoncentration (glykogen + glukos) mätt i M. longissimus 30 min efter slakt för både kron- och dovhjort. Ett linjärt samband mellan pH-värde och koncentration av mjölksyra i M. longissimus kunde också visas. Vi fann en mycket stor varitation i glukoskoncentration (18−123 mmol/kg våtvikt) när köttets pH-värdet var 5,8 eller lägre. Det behövs fler undersökningar för att vidare klargöra sambanden mellan glykogeninnehåll i muskulaturen och teknologisk och sensorisk kvalitet i olika typer av hjortkött.